2014
DOI: 10.1002/jbm.a.35350
|View full text |Cite
|
Sign up to set email alerts
|

High‐strength poly(para‐phenylene) as an orthopedic biomaterial

Abstract: Yield strength 5 92.0 6 4.6 MPa; Fracture strength 5 77.2 6 5.1 MPa; Modulus (E) 5 3104 6 163 MPa; Fracture strain 5 11.1 6 3.5%. 2. On page 3125, the line saying "PEEK experienced plateauing at 0.47 wt.% after 453 days" needs to be altered to: "PEEK experienced a plateau followed by a slight increase to 0.85 wt.% after 276 days". 3. On page 3125, the line saying "However, PEEK had a significant increase in strain to failure values." needs to be removed as that is not the case. 4. On page 3128, the line saying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Previous work has shown that PrimoSpire PR-250 consists of an aromatic backbone with aromatic side groups (Frick et al, 2014). Sodium chloride (NaCl) was purchased from Sigma-Aldrich Co. LLC (St. Louis, MO) and was separated by a sifting process to attain the desired crystal size appropriate for this study (420-500 mm).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work has shown that PrimoSpire PR-250 consists of an aromatic backbone with aromatic side groups (Frick et al, 2014). Sodium chloride (NaCl) was purchased from Sigma-Aldrich Co. LLC (St. Louis, MO) and was separated by a sifting process to attain the desired crystal size appropriate for this study (420-500 mm).…”
Section: Methodsmentioning
confidence: 99%
“…They showed that water absorption was less than 1% after 44 days of soaking and a little-to-no effect was observed on the mechanical properties. Further testing by some of the current authors revealed that the mechanical properties stayed within one standard deviation of dry conditions after soaking in an aqueous environment for over 1 year (Frick et al, 2014). The bulky side groups within the structure of PPPs act as diffusional barriers that prevent water molecules from swelling the polymer (Barnes et al, 1988;Corkhill et al, 1987), resulting in negligible effects on the mechanical properties.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations